A aplicação das regras de impenhorabilidade no metaverso sob a ótica da proteção da dignidade da pessoa humana - Peña, Ricardo Chemale Selistre (2024)
The present study constitutes an analysis and systematization regarding the application of unseizability rules to especific virtual assets maintained in the metaverse, under the premise of human dignity protection. As such, placing the topic within the procedural scope, the study examines the institution of patrimonial responsibility and the restrictions imposed on it due to observation of the principle of human dignity, emphasizing the most contoversial issues, notably the one concerning the possibility of extensive interpretation of the rules established in article 833 of the Civil Procedure Code (CPC), depicting the doctrinal and jurisprudential panorama related to the theme. It delves into the metaverse to unravel its essence and allure, as well as its resemblance to the real world and the reasons that lead a human being to deep immersion in the virtual universe. It is concluded that in the metaverse, assets represented by non-fungible tokens, given certain conditions and through careful consideration, may deserve unseizability protection, even if not considered as unseizability by law, because although virtual, their extraction from the patrimonial sphere violates the human dignity of the debtor.